Energy conservation opportunities in pulp and paper industry : a case study in P.R. China - Guo, Hong; Bhattacharya, Sribas C.; Karmazsin, Etienne; Chen, Xavier; European Union (Bangkok : Asian Institute of Technology, 1994)
An overview of current status of the pulp and paper industry of People's Republic of China (PRC) has been presented in this thesis. The overview shows that the industry is marked by high energy consumption and enormous environmental problems. A study on the energy consumption pattern and the energy conservation potential as well as waste water treatment in a pulp and paper mill in Liaoning Province, PRC, which have a production capacity of 132,000 tons of pulp and paper per year has also been carried out. The average energy intensity is 46.2 GJ/ton paper with specific energy cost of 732 RMB {u00A5}/ton paper. The energy analysis has been carried out for the boiler house unit and the first law efficiency of the boilers has been estimated by identifying the major losses. The potential of energy saving by controlling excess air as well as flue gas temperature is around 186,732 GJ per year. The feasibility study of condensate recovery from the paper machines has been carried out; the results show that the recovery would be economically attractive with a payback period of 1.79 years and IRR of 65.62 %. The feasibility study of anaerobic digestion process for treating pulping waste water has been carried out. The saving that may be possible from the recommended measures is around 4.6 million RMB{u00A5} per year or about 7.5 % of the total energy cost in 1993.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Energy conservation -- China